Disputando espaço, construindo sentidos: vivências, trabalho e embates na área da Manaus moderna (Manaus/AM 1967-2010) - Silva, Patrícia Rodrigues da (2011)
This doctoral thesis discusses the transformations by which the city of Manaus has passed since the execution of a Free Trade Zone in the late 1960 until the present day. Starting from a reflection on the changes in a specific space, the area now called Manaus Moderna , this research seeks to understand the social and historical meanings of these changes and how they were seized and what meanings they had for the different social groups that constitute it. From a wide range of sources such as newspapers, photographs, oral sources and official sources, we performed an analysis of changes in this space, to reflect, above all, the moments of greatest stress. Thus, analyzing plans for recent interventions, such as Town Centre Living and Clash of Order , and talking to workers who work in that spaciousness, undertook a discussion about changes in the assumptions of public policies on intervention in public space, the meanings attributed to that area by some social groups and how they understand and treat these interventions. The research aims to reflect, too, upon the meanings of the construction of Beira Rio Avenue (Manaus Moderna Avenue), which, having been planned in the 1970s, was not carried over from 1980, from a project modernizing developed by the state sector, in order to adapt the city to the new reality of the Free Trade Zone (the Project Manaus Moderna ). It is analyzed also from the memories of stallholders, their photographic collections news and in newspapers of the time, the meanings, tensions and disputes in these two important moments in the transformation of the dynamics of the current area of Manaus Moderna occurred in the interstitium from 1980 to 1991, namely the deactivation of the well-known Staircase s Fair and the implementation of Fair Jorge Teixeira (Manaus Moderna). It was possible to see, before this study that this area also is configured as an area of dispute for different social groups that go there by printing their brands and building the city daily